Biochemistry & Molecular Biology of Plants - Buchanan, Bob B Gruissem, Wilhelm (I.K. International, 2000)
This book is useful for teaching and for reference. It is intended to serve plant biology and related disciplines, ranging from molecular biology and biotechnology to biochemistry, cell biology, physiology, and ecology. Researchers in the pharmaceutical, biotechnology, and agribusiness industries will find a wealth of information inside.